Analysis of the Implementation of the Integrated Dynamic Archival Information System (SRIKANDI) Application in Local Government Agencies within South Barito Regency - Yeni Maficasari (Journal Research of Social Science, Economics, and Management, 2026)
The implementation of electronic-based government systems, such as the Integrated Dynamic Archival Information System (SRIKANDI), is critical for enhancing the efficiency and effectiveness of archival management in local governments. South Barito Regency has initiated the use of SRIKANDI to digitize archival processes, improving the management of incoming and outgoing documents. This research aims to evaluate the efficiency and effectiveness of SRIKANDI application implementation in South Barito Regency's regional offices, identifying both the benefits and challenges of the system. A mixed-methods approach was employed, combining qualitative data from interviews with 10 Regional Apparatus Organizations and quantitative data from the use of SRIKANDI across these offices. The study found that while the system has improved document processing speed, reduced paper usage, and streamlined workflows, significant challenges remain. These include inadequate infrastructure, insufficient training, and the continued use of paper documents in some offices. The findings suggest that further investments in infrastructure and comprehensive training programs are needed to optimize the SRIKANDI system. Additionally, the research highlights the importance of consistent implementation and monitoring across all sectors to ensure the system's success. The implications of this study contribute to understanding the hurdles and strategies for effective implementation of digital archiving systems in local governments, which could be beneficial for future digital transformation initiatives in other regions of Indonesia.